The Effect of Fiscal Policy on Capital Flight in Namibia - Valdemar J. Undji; Teresia Kaulihowa (Journal of Economics and Behavioral Studies, 2019)
The occurrences of capital flight continue to be of great concern for many developing countries and Namibia is not an exception to this. This study aimed at examining the effect of fiscal policy on capital flight in Namibia for the period, 2009-2018. To assess this, the Auto-Regressive Distributive Lag (ARDL) bound test to cointegration technique was employed. The finding revealed that there is a long-run relationship between the selected macroeconomic factors and capital flight. In particular in the long-run government expenditure and its interaction with debt stock are found to positively affect capital flight. In the short-run however, past capital flight, previous period tax rates, previous external debt, current debt stock, previous inflation rate, as well as previous financial deepening were found to bear a positive effect on capital flight. Estimate of capital flight using the residual approach shows that Namibia lost about N 42 billion in 9 years through capital flight. This means on average Namibia lost close to N 5 billion in capital flight. These empirical findings, call for serious policy interventions in order to minimize and contain the issue of capital flight in the country.